Oxidation of α,β-Unsaturated Ketones by Organophotocatalysis Using Rhodamine 6G under Visible Light Irradiation: Insight into the Reaction Mechanism - Yoshioka, Eito; Takahashi, Hiroki; Wanibe, Hikari; Hontani, Yukina; Hatsuse, Kouki; Shimizu, Remi; Kawashima, Akira; Kohtani, Shigeru; Miyabe, Hideto (Synthesis, 2021)
The oxidative transformation of α,β-unsaturated ketones was investigated under visible-light-induced photocatalytic conditions using rhodamine 6G as an organophotocatalyst. In this organocatalysis, the mild co-oxidant bromotrichloromethane (BrCCl3) acts not only as a quencher toward the activated photocatalyst species, having reductant properties, but also as a brominating reagent for the intermediate radicals. This study shows that bromine atom transfer from BrCCl3 to intermediate radicals is a key step in the reaction mechanism of our oxidation method.
Keywords: photocatalysis; oxidation; radicals; organocatalysts; ketones